Correlation between HMGB1 expression and drug resistance and prognosis in patients with bladder urothelial carcinoma - Min Xu; Liang Hu; Zhang Chen; Tianyu Liang; Juanjuan Li (Discover Oncology)
Abstract Objective This study aimed to explore the association between circulating HMGB1 mRNA expression and clinical pathological characteristics and prognosis in bladder urothelial carcinoma (BUC) patients. Methods Circulating HMGB1 mRNA expression levels were assessed using real-time fluorescence quantitative PCR, and patients were categorized into low-expression and high-expression groups based on the median value. Follow-up was conducted for 3 years post-surgery, and patients were classified into non-recurrence and recurrence groups. Baseline circulating HMGB1 mRNA expression levels were compared across different clinical pathological characteristics and prognosis groups to evaluate prognostic disparities based on HMGB1 mRNA expression levels. The Western Blot (WB) experiment assesses the expression levels of HMGB1 across various tissue sections and evaluates the inhibitory effects of chemotherapeutic agents on HMGB1. Additionally, after knocking out HMGB1 in vitro cell lines, the cell proliferation is detected. Results There were no significant differences in HMGB1 mRNA expression levels among patients with varying differentiation grades, lymph node metastasis stage (N stage), primary tumor stage (T stage), or tumor diameter. However, baseline circulating HMGB1 mRNA expression levels were notably lower in surviving patients than in deceased patients. Kaplan–Meier survival analysis revealed a median survival time of 356 weeks in the low-expression group and 259 weeks in the high-expression group. Notably, the low-expression group exhibited significantly prolonged survival compared to the high-expression group (HR = 1.714, 95%CI 1.226, 2.397). WB test showed that the expression level of HMGB1 in tumor tissues of BUC patients was increased, and inhibition of HMGB1 expression could also inhibit the proliferation of tumor cells. Some common chemotherapy drugs can also significantly inhibit the proliferation of BUC cells. Conclusion HMGB1 is highly expressed in urinary bladder epithelial carcinoma, and chemotherapy drugs can effectively inhibit the expression of HMGB1. Inhibition of HMGB1 expression is helpful to inhibit the proliferation of tumor cells. Circulating HMGB1 mRNA expression levels are closely associated with tumor prognosis, with low-expression patients having a longer survival period.